VIRULENSI NUCLEAR POLYHEDROSIS VIRUS (NPV) TERHADAP ULAT GRAYAK (Spodoptera litura F.) (Lepidoptera : Noctuidae) PADA TANAMAN TEMBAKAU DELI DI RUMAH KACA - Rimadhani, Ade Sartika; Bakti, Darma; Tobing, Maryani Cyccu (Jurnal Agroekoteknologi, 2013)
The Virulence of Nuclear Polyhedrosis Virus (NPV) of Tobacco Caterpillar (Spodoptera litura F.)(Lepidoptera : Noctuidae) on Deli Tobacco In Glasshouse. Spodoptera litura(Lepidoptera : Noctuidae) is one important of pests on Deli tobacco. This research was study thevirulence of Nuclear Polyhedrosis Virus of larvae S. litura on Deli tobacco in Glasshouse. Thisresearch was carried out at Central Research Deli Tobacco Sampali PTPN II Medan fromMay to September 2012. The method of this research was Randomized Complete Design Factorialwhich consists stages of larvae (2nd and 4th instar) and the number of virus suspenses (10, 20, and 30larvae infected virus/1 l water) with three replications. The results showed that highest percentagemortality (91.67%) was found in treatment 2nd instar with suspense 30 larvae infected virus/1 l waterand the lowest percentage (0%) on control. The highest percentage of damage intensity (33.06%)was control and the lowest percentage (15.58%) on suspense 30 larvae infected virus/1 l water. Thefastest incubation period in the treatment 4th instar are I.67 days and suspense of 30 larvae infectedvirus/1 l water are 1.83 days and the lowest in the treatment 2nd instar are 2.58 days and controldidn’t showed symptoms infection.